2011
DOI: 10.2134/jeq2010.0079
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary Antimicrobials in Feedlot Manure: Dissipation during Composting and Effects on Composting Processes

Abstract: Composting of manure may lead to the degradation of veterinary antimicrobials, but it is largely unknown if the presence of antimicrobials affects the composting process. Open-air windrow composting of manure from beef cattle (Bos taurus) administered chlortetracycline, sulfamethazine, and tylosin was investigated in a 2-yr study. At windrow construction, chlortetracycline had extensively isomerized to iso-chlortetracycline. Sulfamethazine, tylosin, and iso-chlortetracycline dissipated by first-order kinetics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
67
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 45 publications
12
67
1
Order By: Relevance
“…Although composting has been proposed as a mean to reduce antibiotic levels in manure before land application, recent studies have indicated that it cannot completely remove antibiotics (Dolliver et al, 2008;Cessna et al, 2011;Ray et al, 2017). A major concern is that antibiotics released into soils could exert a selective pressure on the native microbial community (Cleary et al, 2016;Nordenholt et al, 2016) and enrich antibiotic resistant bacteria and resistance genes (Jechalke et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although composting has been proposed as a mean to reduce antibiotic levels in manure before land application, recent studies have indicated that it cannot completely remove antibiotics (Dolliver et al, 2008;Cessna et al, 2011;Ray et al, 2017). A major concern is that antibiotics released into soils could exert a selective pressure on the native microbial community (Cleary et al, 2016;Nordenholt et al, 2016) and enrich antibiotic resistant bacteria and resistance genes (Jechalke et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, the combination of wet manure and cooler air temperatures at the time of windrow construction delayed heating and lowered CO 2 and CTC44SMZ44 were similar to the Control, but higher than CTC44 in 2006. The lack of significant effects of antibiotics on CH 4 emissions observed in our study may be due to low concentrations of residual antibiotics in manure (\0.9 mg kg -1 for CTC, \0.04 mg kg -1 for TYL and\0.3 mg kg -1 for SMZ, Cessna et al 2010). As 2005 was a much wetter year, more prevalent anaerobic conditions should have favored CH 4 production.…”
Section: Carbon Dioxidementioning
confidence: 58%
“…This indicates that manure in CTC11 and CTC44SMZ44 treatments decomposed more rapidly (releasing CO 2 ) Nutr Cycl Agroecosyst (2011) Stone et al (2009). In a concurrent study, Cessna et al (2010) reported a significantly higher temperature increase (20.6°C) after turning on Day 28 for the CTC44SMZ44 than the Control (13.9°C), suggesting that heightened microbial activity may have resulted in the higher CO 2 emissions in 2006. An increase in CO 2 emissions during composting of manure that contains residual levels of CTC or SMZ is inconsistent with the results of others who reported that decomposition was reduced in manure from cattle fed 70 mg hd -1 day -1 of CTC (Elmund et al 1971) and not affected in manure from calves provided with 22 mg kg -1 day -1 of oxytetracycline (Arikan et al 2007).…”
Section: Carbon Dioxidementioning
confidence: 95%
See 1 more Smart Citation
“…Evidence suggests that thermophilic composting is effective at degrading or otherwise deactivating antibiotics in livestock ma-nure (14)(15)(16)(17)(18)(19)(20). The reduction of extractable antibiotics during the compost process appears to be due to abiotic factors such as temperature, pH, and sorption kinetics, although bacteria are likely responsible for some biotic decomposition of antibiotics as well (15,17,21).…”
mentioning
confidence: 99%